Gene transfer-based strategies for heart regeneration - Crottogini, Alberto José (2009)
Ischemic heart disease is the leading cause of mortality worldwide. Its most frequent and serious complication is acute myocardial infarction, after which the remaining contractile tissue undergoes a process characterized by myocyte hypertrophy and death of the remaining myocardium, and its progressive replacement by fibrosis (Sutton and Sharpe 2000). This process, termed remodeling, eventually leads to left ventricular dilation and heart failure. The extent of remodeling is largely dependent upon infarct size (Lenderink et al. 1995). Small infarcts do not induce significant remodeling. Large ones, contrarily, provoke substantial remodeling and therefore evolve towards contractile failure. This explains why regenerating the contractile tissue, a process named cardiomyogenesis, has become a major objective in biomedical research.